THE IJTIHAD OF MUHAMMADIYAH ON THE SPREAD OF THE COVID-19 OUTBREAK IN INDONESIA - Ashfa Afkarina (Jurnal Al-Dustur, 2022)
This article wants to discuss the Ijtihad of Muhammadiyah in the Covid-19 pandemic outbreak in Indonesia. In order to achieve this goal, with a literature approach, this article will answer two important questions, namely how the efforts of Ijtihad Muhammadiyah deal with the Covid-19 outbreak, then furthermore, why the context of Muhammadiyah ijtihad is very important, and in any form ijtihad from Muhammadiyah. Indeed, scholars pay great attention to this ijtihad problem, Muhammadiyah people pay attention to the Muhammadaiyah circular, but the focus of this article has not been a concern for the Muhammadiyah community. Therefore, this study is the first step to exploring the problem. This article argues that in its ijtihad, Muhammadiyah issued ijtihad, replacing Friday prayers with zuhr prayers and jama'ah prayers replaced with prayers in their respective homes, the worship of funeral prayers instead of ghaib prayers, takziah activities carried out online. In treating Muhammadiyah corpses, it is argued that it should be considered to follow health protocols if it is considered an emergency to avoid direct contact with the family or medical personnel with Covid-19 corpses; the body is buried without having to be bathed and shrouded. This is done on the basis of avoiding the immudharotan takes precedence over bringing benefits. It is also based on the hadith that states there is no harm and youth. Religious orders must be carried out efficiently and should not be emphasized if there are uzur, such as during the Covid-19 pandemic.